2017
DOI: 10.1590/abd1806-4841.20175435
|View full text |Cite
|
Sign up to set email alerts
|

Trichotillomania: a good response to treatment with N-acetylcysteine

Abstract: Trichotillomania is considered a behavioral disorder and is characterized by the recurring habit of pulling one's hair, resulting in secondary alopecia. It affects 1% of the adult population, and 2 to 4.4% of psychiatric patients meet the diagnostic criteria. It can occur at any age and is more prevalent in adolescents and females. Its occurrence in childhood is not uncommon and tends to have a more favorable clinical course. The scalp, eyebrows and eyelashes are the most commonly affected sites. Glutamate mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 6 publications
(18 reference statements)
0
18
0
1
Order By: Relevance
“…N-acetylcysteine may be used, as this glutamate-modulating agent is a promising treatment option that can avoid side effects of selective serotonin reuptake inhibitors. A good response was seen in several reported cases [11].…”
Section: Answermentioning
confidence: 79%
“…N-acetylcysteine may be used, as this glutamate-modulating agent is a promising treatment option that can avoid side effects of selective serotonin reuptake inhibitors. A good response was seen in several reported cases [11].…”
Section: Answermentioning
confidence: 79%
“…Grant et al [7] evaluated the efficacy of NAC from 1,200 to 2,400 mg/day in a double-blind, placebo-controlled study on 50 adult patients with trichotillomania, and they observed a significant reduction of hair pulling compared to placebo. Similarly, there are several case reports of patients with trichotillomania successfully treated with oral NAC [8-12]. The mechanism of action of NAC in the treatment of OCD is possibly due to its action on the glutamate system: glutamatergic hyperactivity leading to excitotoxicity and oxidative stress has been implicated in the pathogenesis of OCD [13].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…В литературе имеются данные о восстановлении роста волос у пациентов с трихотейроманией при использовании N-ацетилцистеина в дозировке 1200 мг/ сутки в течение 16 недель [3]. Описан опыт успешного применения N-ацетилцистеина в дозировке 1200-2400 мг/сутки при обсессивно-компульсивном расстройстве, ряде психодерматологических заболеваний (пруриго, онихотилломания, трихотилломания) [20][21][22][23][24][25][26]. Механизм действия N-ацетилцистеина основан на его влиянии на глутамат-систему: в печени N-ацетилцистеин конвертируется до цистеина, который переходит в глутатион, обладающий антиоксидантным эффектом [26].…”
Section: аллергические реакции: пищевые консервантыunclassified